Design of 200V n-type superjunction lateral insulated gate bipolar transistor on partial silicon on insulator - Kho, Elizabeth Ching Tee (Universiti Malaysia Sarawak (UNIMAS), 2014)
Lateral insulated-gate bipolar transistors (LIGBTs) have long been proposed for use in integrated Power Integrated Circuits (PICs). LIGBTs can be fabricated on either bulk silicon substrate or silicon-on-insulator (SOl). The later have been favored by most Integrated PICs due to its superior isolation. However, there are some weaknesses associated with SOl LIGBTs such as reduced Reduce Surface Field (RESURF) effect, higher forward voltage drop (VON), more severe self heating as weU as undesired back-gate and side-gate impacts. The partial SOl (PSOI) concept is subsequently proposed to improve the existing weaknesses in SOl technology such as alleviates the crowding effect of the electrical potential lines in the confined silicon and dissipates the heat more effectivelj For most high voltage (HY) double-diffused metal-ox ide-semiconductor field effect transistor (OMOS) structures, RESURF is the main concept applied to optimize the trade-off in getting high breakdown voltage (BY) and low specific on resistance (RON). The introduction of superjunction concept featuring alternating nand p layers in the drift region proved to be effective in breaking the 'silicon limit' and resulted in drastically reduced RON DMOS. A charge baJanced superjunction allows the depletion of the entire drift region happens at a lower voltage which yields a uniform electric field distribution. The superjunction concept with nand p layers arranged in the device width direction was later extended into both discrete IGBTs and LIGBTs. The main motivation of this research is to design and realize a LIGBT that combines the superjunction with nand p layers arranged in lateral direction approach with the PSOI concept. To realize the superjunction LIGBT, a minimum one additional mask layer is added to the O.18f..lm partial SOl HV process. This work presents and delivers a novel superjunction LIGBT with BV of 220V, Von of 1.55V, 1.75V and 2.30V at 100Ncm2, l50Ncm2 and 300A/cm2 respectiveJy. The measured turn-off time is 130ns under clamped inductive switching circuit. The device is also evaluated at higher temperature and found to have negligible VON increase with the increase of temperature up to 448K. This research work well proving the success in combining the superjunction and partial SOl into a LlGBT device.